2018
DOI: 10.1590/1807-3107bor-2018.vol32.0119
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of toxicity and oxidative DNA damage of sodium hypochlorite, chitosan and propolis on fibroblast cells

Abstract: The objective of this study was to evaluate and compare the cytotoxicity and genotoxicity on human fibroblast cell lines of sodium hypochlorite (NaOCl), chitosan and propolis as root canal irrigating solutions. Human fibroblast cells were exposed to chitosan, propolis and NaOCl for 4 and 24 h. Cell viability was assessed by 2,3-bis-(2methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide, and oxidative DNA damage was assessed by determination of 8-hydroxydeoxyguanosine (8-OHdG) level with an ELISA kit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
(38 reference statements)
0
18
0
1
Order By: Relevance
“…Raman bands assigned to zirconium oxide were present in AH Plus®, EndoSequence® BC Sealer™, and BioRoot™ RCS. It has been reported that ZrO 2 increases radiopacity and does not affect the setting of tricalcium silicate cements in controlled amounts [ 31 ]. Interestingly, ZrO 2 has been related to a greater and longer release of calcium ions of di- and tricalcium silicate-based materials, maintaining long-term bioactivity [ 18 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raman bands assigned to zirconium oxide were present in AH Plus®, EndoSequence® BC Sealer™, and BioRoot™ RCS. It has been reported that ZrO 2 increases radiopacity and does not affect the setting of tricalcium silicate cements in controlled amounts [ 31 ]. Interestingly, ZrO 2 has been related to a greater and longer release of calcium ions of di- and tricalcium silicate-based materials, maintaining long-term bioactivity [ 18 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted apigenin as a flavonoid with considerable antibiofilm potency (Nani et al, 2018;Palomino et al, 2009) due to its ability to increase the permeability of the bacterial membrane, resulting in cellular apoptosis (Zeng et al, 2010). Other studies have highlighted the potential of flavonoids to inhibit the formation of the extracellular polymeric matrix, exposing cells that form biofilms and increasing their susceptibility to antimicrobial therapies (Aydin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It can be successfully used as a chelating substance [ 51 , 52 , 53 , 54 , 55 ], as a scaffold for the delivery of growth factors [ 56 ], or medications [ 57 ]. Moreover, it can be used as an irrigant solution [ 47 , 58 , 59 , 60 ] with less toxicity than sodium hypochlorite or chlorhexidine [ 58 , 59 ], as an intracanal medication by itself [ 61 ], or as an adjunct to calcium hydroxide [ 62 , 63 ]. Chitosan can increase the antibacterial efficacy, bond strength, and penetration of root canal sealers, directly or indirectly [ 48 , 64 , 65 , 66 ].…”
Section: Pulp and Periapical Lesionsmentioning
confidence: 99%